Transcriptional abnormalities in induced pluripotent stem cell-derived oligodendrocytes of individuals with primary progressive multiple sclerosis - Plastini, Melanie J.; Desu, Haritha L.; Ascona, Maureen C.; Lang, Anna L.; Saporta, Mario A.; Brambilla, Roberta (Frontiers in Cellular Neuroscience, 2022)
Multiple sclerosis (MS) is the most common neurological disorder in young adults and is classically defined as a chronic inflammatory demyelinating disease of the central nervous system (CNS). Although MS affects millions of people worldwide, its underlying cause remains unknown making discovery of effective treatments challenging. Whether intrinsic or extrinsic factors contribute to MS initiation and progression is still unclear. This is especially true for primary progressive MS (PPMS), the rarest form of the disease, in which progressive and irreversible loss of neurological function is often observed in the absence of an overt immune-inflammatory response. To test the hypothesis that intrinsic dysfunction in oligodendrocytes (OLs), the primary targets of damage in MS, may contribute to PPMS etiopathology, we differentiated human induced pluripotent stem cell (hiPSC) lines derived from PPMS and healthy individuals into mature OLs to compare their transcriptional profile. PPMS derived OLs displayed hundreds of differentially expressed genes compared to control OLs, many associated with cell adhesion, apoptosis and inflammation, including the inflammasome component Nlrp2, which was highly upregulated. NLRP2 immunoreactivity in OLs was confirmed in post-mortem PPMS brain tissues, with higher expression than in control tissues. Altogether, our findings suggest that mature OLs in PPMS affected individuals carry intrinsic abnormalities that could contribute, at least in part, to the pathophysiology of this form of the disease.